Seeing the person before the numbers: Personas for understanding patients' life stories when using patient-reported outcome measures in practice settings. (April 2023) - Kwon, Jae-Yung; Moynihan, Melissa; Lau, Francis; Wolff, Angela C.; Torrejon, Maria-Jose; Irlbacher, Geraldine; Hung, Lillian; Lambert, Leah; Sawatzky, Richard
Abstract: Aims: While patient-reported outcome measures (PROMs) are increasingly being integrated into health information technologies, one challenge has been to assist clinicians in understanding how the responses to PROMs relate to patient stories for identifying and addressing the care needs of individual patients. Personas, hypothetical representations of patients, can be used as an innovative strategy to support clinicians' use of PROMs in their practice. These personas embody patients' life stories, making them a valuable tool for understanding the person when using PROMs. The aim of this project focused on cancer-related experiences to develop personas as a knowledge translation strategy to support clinicians' use of PROMs for person-centred cancer care. Methods: Eight older adults participated in online workshops (n = 2–3 participants/workshop; 1.5-hour sessions) to co-develop personas that reflected their collective experiences at a particular stage of their cancer journeys. Participants were asked to identify themes that focused on what the personas were thinking and feeling, what influenced how the personas acted, and the personas' overall goals. Participants subsequently completed an emotional well-being PROM from the perspective of the persona. Personas were further refined based on key themes identified during the workshop discussions. Results: Four personas representing the cumulative experiences of the workshop participants were developed to help clinicians link PROM responses to patient stories. These personas became the basis of four practice scenarios, which were examples of interactions between a clinician and each persona, to demonstrate the use of PROMs in practice. Conclusion: Personas can be used to illustrate patients' life stories and contextualize PROMs data. As a knowledge translation strategy, personas can foster clinician awareness of how responses to PROMs can be used to initiate conversations to better understand patients' unique life situations.